The Appearance of False Sign in Ads at Social Media - Ilhamsyah, Ilhamsyah; Herlina, Herlina (Universitas Swadaya Gunung Jati, 2016)
The aim of this study is to determine the presence of signs and combinations ofsigns (codes) that are present on the fictitious figure of Sarah Aprilia in Cologne Baskadvertising on the internet. The sign and the code in general should have a commonunderstanding by prospective readers (target audience). This research used qualitativeapproach with interpretative descriptive method because semiotic science is diggingand discovery the meaning. In analyzing the fictitious figure of Sarah Aprilia, the signthat appearance is false sign. Deceptive mark is a sign that unknown origin , but theengineering rests on a natural object (hybrid), but viewers assume it was real presence.This is due to the many cross signs presented visual codes that make the figure of SarahAprilia as a real figure.